2016
DOI: 10.4314/ovj.v6i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Urinary capillariosis in six dogs from Italy

Abstract: Canine urinary capillariosis is caused by the nematode Pearsonema plica. P. plica infection is seldomly detected in clinical practice mainly due to diagnostic limitations. This report describes six cases of urinary capillariosis in dogs from Italy. Recurrent cystitis was observed in one dog, whereas another patient was affected by glomerular amyloidosis. In the remaining animals, the infection was considered an incidental finding. Immature eggs of the parasite were observed with urine sediment examination in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 17 publications
2
24
0
2
Order By: Relevance
“…However, a third urinary capillariid species, namely Capillaria travassoi, has been reported in domestic felids in North America, but it is still not clear whether P. feliscati and C. travassoi should be considered distinct species or the same species [3]. Adults of these capillariids reside in the urinary bladder and, more rarely, in the ureters and renal pelvis of domestic and wild carnivores, in which they may be responsible for urinary capillariosis [4][5][6][7][8]. The host spectrum of P. plica includes wild and domestic canids and felids, while P. feliscati only infects felids [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, a third urinary capillariid species, namely Capillaria travassoi, has been reported in domestic felids in North America, but it is still not clear whether P. feliscati and C. travassoi should be considered distinct species or the same species [3]. Adults of these capillariids reside in the urinary bladder and, more rarely, in the ureters and renal pelvis of domestic and wild carnivores, in which they may be responsible for urinary capillariosis [4][5][6][7][8]. The host spectrum of P. plica includes wild and domestic canids and felids, while P. feliscati only infects felids [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Pathohistological examination showed chronic interstitial nephritis and glomerular amyloidosis, with chronic inflammation of the urinary bladder and renal pelvis, and with mononuclear cells infiltrating the submucosa (Callegari et al, 2010). Mariacher et al (2016) found disseminated fields of tubular necrosis.…”
Section: Pathogenesis and Pathomorphological Signsmentioning
confidence: 99%
“…After manifestations of oliguria and dysuria, some symptomatically similar diseases should be excluded, such as acute and chronic renal insufficiency, urolithiasis, prostate hyperplasia, feline urological syndrome (FUS), cystitis with other aetiology (for example bacteriological) etc. Mariacher et al (2016) pointed out the importance of urinary capillariosis in differential diagnosis of chronic and recurrent diseases of the lower urinary tract and kidneys.…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations